IMPOSISI FATWA TERHADAP REGULASI PERBANKAN SYARIAH: (Studi Komparasi Perbankan Syariah Indonesia dan Malaysia) - Muhammad Majdy Amiruddin (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2018)
The imposition of fatwa as a source of law is varies in every Muslim-majority country. Some consider it as a source of legal hierarchy and government structure. Some of which place it outside the system. The difference also affects the independence of the fatwa as well as the issuing institution. In Brunei Darussalam, fatwa has a very important position because it includes in the legal structure of the country. In Malaysia, its position is very importan too because the position of mufti level under the sultan in religious affairs. In Indonesia itself, fatwas can only bind when absorbed into the legal system prevailing in Indonesia. Different Position fatwa is also affect the regulation of Islamic banking. This study compiles the imposition of fatwas against shariah banking regulations in Indonesia and Malaysia. Qualitative method used in preparing this research. The data were collected from related literature. The results of this study indicate that the position of fatwa in sharia banking regulation in both countries is very significant. In Malaysia, the Fatwa is issued by the Shariah Advisory Council (SAC) directly under the auspices of Bank Negara Malaysia and is binding upon the approval of the Majlis Raja-raja and issued in the form of a gazette. In Indonesia, the Indonesian Council of Ulama issued Fatwas through the badan Pengawas Syariah (DNS) which was then absorbed into Bank Indonesia Regulation (PBI)